Modern trends and priority in treatment of chronic anal fissure - S. A. Aliev; E. S. Aliev (Вестник хирургии имени И.И. Грекова)
The article discusses the current state of the problem and priorities in the treatment of chronic anal fissures according to literature data. We described consistently standard medical, surgical and other treatment methods with an assessment of their advantages and disadvantages. Based on the analysis of literature data, it is shown that fissure excision in combination with dosed form of subcutaneous sphincterotomy still remains the «gold standard» for the treatment of chronic anal fissure. Taking into account the revision of the traditionally established paradigm and the emerging trends towards a multidisciplinary approach to the problem, the use of combined and minimally invasive sphincter-sparing treatment methods is justified. The use of botulinum toxin, various options for anoplasty, transcutaneous neurostimulation, laser vaporization and pneumoballoon dilatation of the anal sphincter are described. The possibilities of using autologous plasma enriched with platelet growth factors and autologous cells of adipose origin used as cell (tissue) transplantation are presented.